2020
DOI: 10.1080/03004430.2020.1806830
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s emotional stress reactions during the COVID-19 outbreak and their associations with parental emotion regulation and parental playfulness

Abstract: Children's emotional adjustment during stressogenic events is highly dependent on their parents' emotional state. The present study explored young children's emotional adjustment during the COVID19 outbreak as it relates to their exposure to stress, and their parents' emotion regulation and playfulness. A sample of 351 Israeli parents of children aged 2-7 years completed online questionnaires. The most frequent stress symptoms in children were nervousness, agitation, and aggression, separation fears and clingi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 46 publications
9
74
0
7
Order By: Relevance
“…Children of preschool age need a direct partner, their communication can be mediated by joint activities with other children, it is then that an occasion arises and a semantic field appears necessary for communication. These data generally match with the estimates of other researchers, made, in particular, on the material of a survey of families in the United States [19]. In general, we share the opinion that if during the lockdown period there is an increase in the time of communication between children and peers through digital technologies, then this was necessarily facilitated by the active organizational role of an adult.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Children of preschool age need a direct partner, their communication can be mediated by joint activities with other children, it is then that an occasion arises and a semantic field appears necessary for communication. These data generally match with the estimates of other researchers, made, in particular, on the material of a survey of families in the United States [19]. In general, we share the opinion that if during the lockdown period there is an increase in the time of communication between children and peers through digital technologies, then this was necessarily facilitated by the active organizational role of an adult.…”
Section: Discussionsupporting
confidence: 87%
“…One of the objectives of this study was to determine the typical patterns of behavior of children and adults in the family, which ensured a positive experience of the COVID-19 lockdown. According to the conclusions made in the works of authors from Turkey and Israel devoted to the problem of the psychological climate in families during time had the ability of parents to organize joint play activities with children [18,19]. Our data confirm this position, and also indicate that it is especially important for parents during this period to be ready to help children in their studies, accompanying children with preschool tasks completion.…”
Section: Discussionsupporting
confidence: 79%
“…The level of academic stress in students has increased with online learning during the Covid 19 pandemic (Shorer & Leibovich, 2020). The dissemination of learning during a pandemic through digital portals will require access to laptops/computers and gadgets for students (Polizzi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The state of students at moderate to severe stress levels can hinder learning (Amin, 2018). Increasing the amount of academic stress will decrease academic ability, which will impact the student achievement index (Shorer & Leibovich, 2020). Other studies have shown that students evaluated during the pandemic period exhibit significantly higher anxiety, depression, and stress than students during regular times (Wang, Zhao, & Maia, 2020 (Shorer & Leibovich, 2020) was used in this study to measure students' stress levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to assess the exact effect these events may have had on the interviews and findings, as the fathers were not asked directly about this topic. Further investigation into the effects of national life-threatening situations on paternal mentalization may be of special relevance due to the COVID-19 pandemic and its implications on parent–child interactions (e.g., Shorer and Leibovich, 2020 ).…”
Section: Discussionmentioning
confidence: 99%